Forensic accounting and fraud examination - Kranacher, Mary-Jo 1952-; Riley, Richard 1962-; Wells, Joseph T. (Wiley, 2011)
A new resource that meets the demand for detailed information on forensic accounting. Presents comprehensive coverage of fraud detection and deterrence, incorporating the most current information in the field This easy to read, comprehensive textbook includes case study examples to clearly explain technical concepts and bring the material to life.